Corporate Social Responsibility and Work Engagement: Mediating Roles of Compassion and Psychological Ownership - Ali, Muhammad (Animo Repository, 2021)
Employee work engagement has become a great challenge for today’s HR managers globally as hardly 13% of employees are engaged in their work. Therefore, this study investigates the mechanism between corporate social responsibility (CSR) and employee work engagement considering compassion at work and psychological ownership as mediators. We collected data from 251 employees working in the life insurance company using a self-administered questionnaire through convenience sampling. We applied structural equation modeling using AMOS version 24 to test the hypotheses. The results reveal a significant direct association between CSR and employee work engagement. Further, compassion at work and psychological ownership were found to partially mediate the association between CSR and employee work engagement. Our study highlights the significance of CSR to increase employee work engagement by experiencing compassion at work and psychological ownership. This research contributes to the existing literature on CSR and micro organizational behavior literature from the social identity perspective. Furthermore, to the best of our knowledge, compassion at work and psychological ownership have not been examined as mediators between CSR and employee work engagement.